2021
DOI: 10.3390/ijms22084117
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of TALE Superfamily Genes in Soybean (Glycine max L.)

Abstract: The three-amino-acid-loop-extension (TALE) superfamily genes broadly existed in plants, which played important roles in plant growth, development and abiotic stress responses. In this study, we identified 68 Glycine max TALE (GmTALE) superfamily members. Phylogenetic analysis divided the GmTALE superfamily into the BEL1-like (BLH/BELL homeodomain) and the KNOX (KNOTTED-like homeodomain) subfamilies. Moreover, the KNOX subfamily could be further categorized into three clades (KNOX Class I, KNOX Class II and KNO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 57 publications
7
27
0
Order By: Relevance
“…By determining the ratios of K a to K s, we were able to characterize the evolutionary history and differentiation paths of CsTALE genes, which indicated that these genes have primarily evolved under the influence of purifying selection, and that KONX subfamily members appeared later than those in the BEL subfamily. These evolutionary patterns of CsTALE gene origin and divergence are similar to those reported for G. max , which thus tends to indicate that TALE gene families have evolutionarily conserved mechanisms and functions ( Wang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…By determining the ratios of K a to K s, we were able to characterize the evolutionary history and differentiation paths of CsTALE genes, which indicated that these genes have primarily evolved under the influence of purifying selection, and that KONX subfamily members appeared later than those in the BEL subfamily. These evolutionary patterns of CsTALE gene origin and divergence are similar to those reported for G. max , which thus tends to indicate that TALE gene families have evolutionarily conserved mechanisms and functions ( Wang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 77%
“…In lines with expectations, as TFs, all identified Cs TALE members are predicted to be nuclear localized. Similar to the soybean and poplar TALEs, we found that the number of amino acid residues and MWs of KNOX subfamily Cs TALEs are considerably smaller than those in the BEL subfamily ( Zhao et al, 2019 ; Wang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Rice KNOX7 integrates secondary wall and cell growth master regulators in internode and panicle development ( Wang et al, 2019 ). Most soybean KNOX II genes exhibited higher expression levels during saline stress ( Wang et al, 2021 ). Consistent with these results, the present expression analysis of GhKNOX3a , GhKNOX5b and GhKNL1 showed prior expression in the fiber, and GhKNL1 affected fiber development in the secondary cell wall biosynthesis pathway ( Gong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional research has revealed that KNOX genes are involved in abiotic stress responses. In soybean, most KNOXII genes exhibit higher expression levels in response to saline stress and dehydration ( Wang et al, 2021 ). GmSBH1 , a member of the KNOXI clade, is involved in the response to high temperature and humidity stress in soybean seed development ( Shu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%